Simplified shear force-chord rotation relationship for concrete-filled steel plate composite coupling beams. (January 2022) - Mansouri, Ali; Najafi, Hasan
Highlights: Providing a model for the shear force-chord rotation relation of CFSP coupling beams. Development of a numerical model for predicting the seismic behavior of CFSP coupling beams. Proposing equations for calculating the effective stiffness of CFSP coupling beams. Providing suggestions for calculating the maximum and yield strengths of CFSP coupling beams. Abstract: Concrete-filled steel plate (CFSP) composite coupling beam is a new type of coupling beam with large deformation and energy dissipation capacity. Given the need for shear force-chord rotation envelope curve of the coupling beam in the general modeling and analysis of coupled CFSP composite shear wall structures, this paper presents an envelope curve for CFSP composite coupling beams based on the results of nonlinear finite element analysis. A comparison between the results of finite element analysis (FEA) and the existing experimental data demonstrates the ability of the numerical model to accurately predict the shear force-chord rotation hysteresis curve and the local response of CFSP composite coupling beams. To gather sufficient data for plotting the envelope curve, multiple numerical models with different values assigned to the span/depth ratio, web plate thickness, flange plate thickness, and compressive strength of the concrete are analyzed under cyclic lateral loading. The analysis results are used to derive some equations for calculating the effective flexural and shear stiffness of the coupling beam based on the stiffness of steel plates and concrete infill, with a reduction coefficient applied to the stiffness contribution of the concrete. Some suggestions are provided for calculating the maximum and yield strengths of the coupling beam, based on the minimum strength corresponding to shear failure and flexural capacity. Finally, the analysis results are used to provide a trilinear model for the shear force-chord rotation hysteresis envelope of CFSP composite coupling beams.